Conjunctive Analyses of Bulk Segregant Analysis Sequencing and Bulk Segregant RNA Sequencing to Identify Candidate Genes Controlling Spikelet Sterility of Foxtail Millet - Gao, Yongbin; Du, Lihong; Ma, Qian; Yuan, Yuhao; Liu, Jinrong; Song, Hui; Feng, Baili (Frontiers in Plant Science, 2022)
Foxtail millet has gradually become a model crop of gramineous C4 crops due to its short growth period and small genome. Study on the development of spikelets is not only directly related to the yield and economic value of foxtail millet but also can provide a reference for the fertility study of other C4 crops. In this study, a hybrid population containing 200 offspring was constructed by Xinong8852 and An15, and two extreme trait populations were constructed for the spikelet sterility and normal traits with F2. BSA-Seq was used to determine the candidate regions and candidate genes related to the development of foxtail millet spikelets. And the functional analysis of DEGs in populations with different traits was carried out by BSR-seq. Finally, conjunctive Analyses BSA-Seq and BSR-Seq results, and combined with biological information analysis, six genes on chromosome 7 were finally identified as candidate genes for controlling foxtail millet spikelet development. This study provides a new reference for the study of foxtail millet sterility and lays a solid foundation for the future fertility study of gramineous crops.